Optimization of Location Assignment for Unit-Load AS/RS with a Dual-Shuttle - Cunkas, Mehmet; Ozer, Osman (International Journal of Intelligent Systems and Applications in Engineering, 2019)
Automated Storage and Retrieval Systems (AS/RS) offer several advantages such as gaining space, reducing human errors, and completing more storing and retrieving tasks in less time to large size warehouses. Machines included multi-shuttle systems are designed to carry multiple loads in one cycle on the purpose of develop the performance. This paper deals with a quadruple command cycle location assignment method in unit-load dual-shuttle AS/RS. Also, it is shown how to solve location assignment problem using Particle Swarm Optimization (PSO) with the objective of shortest travel distance therewithal shortest travel time. Binary Coded Genetic Algorithm (BGA) and Real Coded Genetic Algorithm (RGA) are developed to validate result obtained. At the end, ten numerical examples for two scenarios designed small size and large size are presented to prove the implementation of the proposed method. Results showed that PSO accomplished to find optimal solution for shortest travel distance of AS/RS machine.